Maternal reproductive senescence shapes the fitness consequences of the parental age difference in ruffed lemurs. Issue 1886 (12th September 2018) - Tidière, Morgane; Thevenot, Xavier; Deligiannopoulou, Adamantia; Douay, Guillaume; Whipple, Mylisa; Siberchicot, Aurélie; Gaillard, Jean-Michel; Lemaître, Jean-François
Abstract : In humans, pronounced age differences between parents have deleterious fitness consequences. In particular, the number of children is lower when mothers are much older than fathers. However, previous analyses failed to disentangle the influence of differential parental age per se from a direct age effect of each parent. In this study, we analyse the fitness consequences of both parental age and parental age differences on litter size and offspring survival in two closely related species of lemurs living in captivity. As captive lemurs do not choose their reproductive partner, we were able to measure litter size and offspring survival across breeding pairs showing a wide range of parental age differences. However, we demonstrated that the effect of the parental age difference on litter size was fully accounted for by female reproductive senescence because females mating with much younger males were old females. On the other hand, both parental age difference and female reproductive senescence influenced offspring survival. Our results emphasize the importance of teasing apart the effect of parental reproductive senescence when investigating the health and fitness consequences of parental age differences and also provide new insights for conservation programmes of endangered species.